Waste biomass assisted synthesis of silicon nanostructures for photoelectrochemical water splitting / Farah Nadiah Nordin - Farah Nadiah , Nordin (2022)
This work reports on the growth of Si nanostructures (nanorods and nanowires) by a chemical vapor deposition technique. The main interest of this work is to utilize the wastebiomass sources for the application of photoelectrochemical water splitting. This work is initiated to transform the biomass into a value-added product as well as to investigate the optimization conditions of Si nanostructures as photocatalyst for the water splitting application. In this work, the effect of variation of SiO2 source masses (15 to 150 mg) on the growth, structural and optical properties of the nanostructures are studied at a fixed deposition temperature of 1410 oC. Si nanorods were prepared at low SiO2 source masses of 15, 25 and 50 mg with an average diameter of about (247 } 22), (55.1 } 5.5) and (221 } 28) nm, respectively. An increase in SiO2 source masses of 100, 125 and 150 mg resulted in the formation of high-density Si nanowires with relatively smaller in average diameter of (31.8 } 3.0), (48 } 4) and (82 } 17) nm, respectively. The microstructure studies of these nanostructures have revealed the perfect single crystal structure of a highly crystalline Si nanowires with a very thin amorphous SiOx layer. Therefore, this resulted in the band gap energies of the Si nanowires and nanorods been tailored within the UV and visible light region showing an excellent visible light absorption capability. Apart from that, this work also highlights on the photoelectrochemical behaviour of asgrown Si nanowires with a better photocurrent density of 0.5 mA cm-2 as compared to asgrown Si nanorods at a potential of 0.6 V in Ag/AgCl aqueous solution. This is attributed to the extremely large surface area and large number of active sites of Si nanowires, which enhancing the water splitting oxidation and reduction reaction processes. The role of silica in facilitating the growth mechanism of these nanostructures were also discussed.